The structural and human resources support for Brazilian Paralympic athletes - Denardin Cardoso, V.; De Castro Haiachi, M.; Reppold Filho, A. R.; Araújo Gaya, A. C. (Journal of Human Sport & Exercise, 2018)
The purpose of this study is to describe the importance of structural and human resources support for Brazilian Paralympic athletes. It is characterized as descriptive and qualitative approach. Data collection was conducted through semi-structured interviews. Twenty Paralympians, from both Athletics and Swimming modalities, participated of this research, all of them contemplated by grant Bolsa Atleta Pódio from Bolsa Atleta program of Ministry of Sports in Brazil. The results show that Structural Support (n = 20; 100%) and Human Resources Support (n = 19; 95%) are considered fundamental by the interviewed athletes. Actions focused on improving training conditions and the support of human resources are fundamental for the development of Paralympic sport and can guarantee the emergence of new generations of Paralympic athletes in Brazil.